2012
DOI: 10.1088/0031-9155/58/2/373
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high intensity terahertz radiation on mammalian cell adhesion, proliferation and differentiation

Abstract: Understanding the influence of exposure of biological systems to THz radiation is becoming increasingly important. There is some evidence to suggest that THz radiation can influence important activities within mammalian cells. This study evaluated the influence of the high peak power, low average power THz radiation produced by the ALICE (Daresbury Laboratory, UK) synchrotron source on human epithelial and embryonic stem cells. The cells were maintained under standard tissue culture conditions, during which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 30 publications
(57 reference statements)
1
29
0
Order By: Relevance
“…By contrast, high-power density THz exposure (0.1-1.0 THz, 2000-14000 mW/cm 2 ) produced tissue damage in wet chamois cloths at a damage threshold of 7160 mW/cm 2 [86], along with an obvious temperature rise. Similar studies on cells also revealed that low-power densities had no adverse effects on the morphology, attachment, proliferation, or differentiation of human ocular cell lines and embryonic stem cells (0.02-0.37 mW/cm 2 [ 4 _ T D $ D I F F ] ) [87], whereas continuous exposure to 84.8 mW/cm 2 power density THz radiation for 80 min was sufficient to raise the temperature by approximately 3 8C and led to almost 10% cell death in human primary dermal fibroblasts [88]. Therefore, tissue damage and cell death can result from the thermal effects of highpower densities [84].…”
Section: Biological Effects: Increasing Concernsmentioning
confidence: 77%
“…By contrast, high-power density THz exposure (0.1-1.0 THz, 2000-14000 mW/cm 2 ) produced tissue damage in wet chamois cloths at a damage threshold of 7160 mW/cm 2 [86], along with an obvious temperature rise. Similar studies on cells also revealed that low-power densities had no adverse effects on the morphology, attachment, proliferation, or differentiation of human ocular cell lines and embryonic stem cells (0.02-0.37 mW/cm 2 [ 4 _ T D $ D I F F ] ) [87], whereas continuous exposure to 84.8 mW/cm 2 power density THz radiation for 80 min was sufficient to raise the temperature by approximately 3 8C and led to almost 10% cell death in human primary dermal fibroblasts [88]. Therefore, tissue damage and cell death can result from the thermal effects of highpower densities [84].…”
Section: Biological Effects: Increasing Concernsmentioning
confidence: 77%
“…Based on the experimental details provided in the paper, we estimate that the energy density per pulse was ~3 pJ/cm 2 (3 × 10 −6  μJ/cm 2 ). In a recent work, Williams et al 17 . explored the influence of more intense THz pulses produced by the ALICE (Daresbury Laboratory, UK) synchrotron source, with energy densities per pulse reaching 10 nJ/cm 2 (0.01 μJ/cm 2 ), on the attachment, morphology, proliferation and differentiation of human epithelial and embryonic stem cells.…”
Section: Discussionmentioning
confidence: 96%
“…At the same time, we are only starting to uncover how THz radiation, and especially intense THz pulses with duration on the order of 1 ps and peak electric fields on the order of 100 kV/cm and higher, interacts with biological tissue111213141516171819. With photon energies typically in the range from 0.5–15 meV, THz radiation is non-ionizing, and the mechanisms by which it interacts with cells and tissues are fundamentally different from those involved in interactions of living matter with high-energy ionizing radiation ( i.e.…”
mentioning
confidence: 99%
“…To date, several investigations have been performed to better understand the biological effects related to THz radiation [5][6][7][8][9][10][11][12][13][14][15][16]. The data from these reports indicates that THz radiation does elicit a variety of biological effects at the organism, tissue, and cellular levels.…”
Section: Introductionmentioning
confidence: 99%
“…The data from these reports indicates that THz radiation does elicit a variety of biological effects at the organism, tissue, and cellular levels. A few of the observed effects include morphological changes (i.e., swelling, blebbing, shrinking), stimulation of cellular growth and metabolic intracellular pathways, activation of cellular stress response mechanisms, and cellular death [5][6][7][8][9][10][11][12][13][14][15][16]. Unfortunately, although many of these studies have been helpful to the THz community, a review of the results indicates that the findings are often conflicting and the THz exposure methodologies used are often not consistent.…”
Section: Introductionmentioning
confidence: 99%